Bond wire lift-off detection by gate voltage waveform in IGBT turn-off process enhanced by digital gate control - Thatree Mamee; Zaiqi Lou; Katsuhiro Hata; Makoto Takamiya; Shin-ichi Nishizawa; Wataru Saito (Power Electronic Devices and Components, 2023)
This paper presents a new detection method of bond wire lift-off in Insulated Gate Bipolar Transistor (IGBT) power module. The bond wire lift-off is a major failure mode in power cycle degradation of the IGBT module, and many monitoring methods have been proposed and demonstrated for safety operation of power electronics systems in the previous works. In this study, we focus on the gate voltage waveform as an indicator to detect wire-lift for a simple and straightforward detection method. Due to the increase in parasitic inductance caused by bond wire lift-off, the turn-off switching waveform becomes modulated. The digital gate control (DGC) was employed to control the switching behavior to obtain precision for low-noise and high-performance. Furthermore, the DGC 2-step vector control (2-sVC) can enhance the sensitivity of bond wire lift-off failure detection by gate voltage waveform change. As feature quantities, the gate voltage spike peak, its amplitude and the timing shift were measured at various operating conditions. The DGC obtained larger feature quantities compared with conventional gate control. In particular, high-current conditions were found to be more favorable for achieving high sensitivity due to the high die/dt. From these results, the DGC is effective to achieve both the high sensitivity to detect bond wire lift-off by gate voltage waveform and maintaining the best switching performance.